BATF-dependent IL-7RhiGM-CSF+ T cells control intestinal graft-versus-host disease - Ullrich, Evelyn; Abendroth, Benjamin; Rothamer, Johanna; Huber, Carina; Büttner-Herold, Maike; Buchele, Vera; Vogler, Tina; Longerich, Thomas; Zundler, Sebastian; Völkl, Simon; Beilhack, Andreas; Rose-John, Stefan; et al. (Journal of Clinical Investigation, 2018)
Acute graft-versus-host disease (GVHD) represents a severe, T cell-driven inflammatory complication following allogeneic hematopoietic cell transplantation (allo-HCT). GVHD often affects the intestine and is associated with a poor prognosis. Although frequently detectable, proinflammatory mechanisms exerted by intestinal tissue-infiltrating Th cell subsets remain to be fully elucidated. Here, we show that the Th17-defining transcription factor basic leucine zipper transcription factor ATF-like (BATF) was strongly regulated across human and mouse intestinal GVHD tissues. Studies in complete MHC-mismatched and minor histocompatibility-mismatched (miHA-mismatched) GVHD models revealed that BATF-expressing T cells were functionally indispensable for intestinal GVHD manifestation. Mechanistically, BATF controlled the formation of colon-infiltrating, IL-7 receptor-positive (IL-7R+), granulocyte-macrophage colony-stimulating factor-positive (GM-CSF+), donor T effector memory (Tem) cells. This T cell subset was sufficient to promote intestinal GVHD, while its occurrence was largely dependent on T cell-intrinsic BATF expression, required IL-7-IL-7R interaction, and was enhanced by GM-CSF. Thus, this study identifies BATF-dependent pathogenic GM-CSF+ effector T cells as critical promoters of intestinal inflammation in GVHD and hence putatively provides mechanistic insight into inflammatory processes previously assumed to be selectively Th17 drive
EVALuna2:25783

Batf-dependent Th17 cells critically regulate IL-23 driven colitis-associated colon cancer - Punkenburg, Elise; Vogler, Tina; Büttner, Maike; Amann, Kerstin Ute; Waldner, Maximilian; Atreya, Raja; Abendroth, Benjamin; Mudter, Jonas; Merkel, Susanne; Gallmeier, Eike; Rose-John, Stefan; Neurath, Markus; et al. (Gut, 2016)
IBDs have an increased risk for development of colorectal cancer (CRC). Here, we aimed at the characterisation of the functional role of Th17-associated transcription factors in sporadic and colitis-associated colon cancer in vivo.We used mice deficient or transgenic for the activating protein 1 family member basic leucine zipper transcription factor ATF-like (Batf) to evaluate the role of Th17 cells during sporadic and inflammation-induced colon carcinogenesis. We also studied the expression of Batf and ROR?t in patients with IBD and CRC.Batf but not retinoic acid-related orphan receptor ?t(ROR?t) expression was significantly increased together with interleukin (IL) 23 expression in UC but not in Crohn's disease (CD) tissue samples. In CRC also Batf but not ROR?t expression was increased and its expression correlated with the IL-23 and IL-23 receptor (IL-23R) expression. Finally, Batf but not ROR?t was coexpressed with IL-17a, IL-23R and IL-6 within CRC-infiltrating CD4(+) T cells. Functional studies in mice revealed that Batf-dependent T cells are crucial regulators of sporadic and inflammation-induced CRC. Colitis-associated Batf(-/-) tumours lacked IL-17a(+)IL-23R(+)IL-6(+)CD4(+) T cells, hence displaying characteristics reminiscent of human CRC-infiltrating CD4(+) T cells. Strikingly, Batf(-/-) tumours contained low IL-23 but high IL-17a expression levels. Tumour formation and intratumoral IL-23 expression could be restored by administration of Hyper-IL-6 consisting of IL-6 and soluble IL-6 receptor.Batf-dependent IL-23R(+)IL-6(+)CD4(+) Th17 cells critically control IL-23 driven colitis-associated tumour formation and the progression of sporadic colon tumours. Batf-dependent IL-23R(+) T cells represent a potential future therapeutic target limiting CRC progression.
EVALuna2:2026

Clearance of primary necrotic cells by non-professional phagocytes - Schwegler, Manuela; Wirsing, Anna Maria; Dollinger, Alena J.; Abendroth, Benjamin; Putz, Florian; Fietkau, Rainer; Distel, Luitpold (Biology of the Cell, 2015)
Homotypic internalisation of tumour cells has frequently been observed in tumour tissue sections. Events of non-professional phagocytosis, however, may also occur in normal tissue if the number of dying cells exceeds the phagocytic capacity of professional phagocytes such as macrophages and dendritic cells. The aim of this study was to investigate the molecular background of non-professional phagocytosis of primary necrotic cells by neighbouring tumour cells and normal skin fibroblasts.We demonstrate that homotypic and heterotypic uptake of necrotic cells is a feature common to various cell types. Investigating critical stimuli of necrotic cell clearance we found that non-professional phagocytes require cytoskeleton rearrangement, recognition of phosphatidylserine and GTPase activity of dynamin II, which is normally engaged in endocytosis. Additionally, we have observed an accumulation of adhesion molecule E-cadherin, phosphorylated actin-linker protein ezrin, lysosomal-associated membrane protein 1 and microtubule-associated protein 1 light chain 3 at the site of engulfment. Loss of membrane integrity and an increase in the intracellular level of heat-shock protein 70 in the necrotic cells have also been observed.Our results shed light on the mechanism of necrotic cell removal by tumour cells and normal skin fibroblasts in vitro. It is reasonable to assume that this process has a physiological relevance in inflammation and autoimmune disease in normal tissue as well as in tumours regarding immune cell infiltration. We conclude that necrotic cell clearance by non-professional phagocytes contributes to the phagocytic activity by macrophages and that this process may prevent release of proinflammatory damage-associated molecular pattern molecules.
EVALuna2:18281

Immunopathogenesis of IBD: Batf as a Key Driver of Disease Activity - Hildner, Kai; Punkenburg, Elise; Abendroth, Benjamin; Neurath, Markus (Digestive Diseases, 2016)
Inflammatory bowel diseases (IBDs) represent a group of chronic immune-mediated disorders that are influenced by a genetic predisposition and additional environmental triggers. Genome-wide association studies strongly implicate that a number of immune system-related genetic variations are critically contributing to the initiation and promotion of intestinal inflammation. Especially the identification of the strong association of a series of single nucleotide polymorphisms including interleukin (IL)-23R, CCR6, signal transducer and activator of transcription 3 (Stat3) and Stat4 with IBD susceptibility point at a critical involvement of T cells and especially of IL-17a-producing Th17 cells in the immune pathogenesis of IBD. In line with this hypothesis, a series of preclinical studies have unequivocally established that T cells are key drivers of immune-mediated colitis. Interestingly, especially Th17 cells were identified to be highly prevalent in inflamed IBD tissues, a finding that seems to be functionally relevant as genetic inactivation studies in the mouse resulted in almost complete suppression of colitis development.While targeting Th17 cell differentiation regulating transcription factors, as retinoic acid-related orphan receptor gamma t (ROR?t) is effective in preventing murine colitis, one concern of drugs targeting ROR?t in a clinical setting represents the large body of murine data unambiguously demonstrating that additional pathways within and outside the immune system are equally ROR?t-dependent increasing the risk of undesirable side effects. The AP1 transcription factor Batf (B cell-activating transcription factor) appears to exclusively regulate pathways within lymphocytes. Importantly, Batf represents a central regulator of Th17 cell development and is strongly upregulated within IBD-affected tissues. Employing 2 acute colitis models, we demonstrate in this study that Batf-expressing T cells are critical drivers of T cell-mediated colitis while in contrast to Stat3 loss of Batf does not affect intestinal epithelial cell homeostasis ex vivo.Targeting Batf in IBD emerges as an attractive therapeutic approach disabling colitogenic T cell activities while sparing off-target effects in the intestinal epithelial cell compartment.
EVALuna2:2187

Intestinal graft-versus-host disease is driven by BATF-dependent IL-7R(hi)GM-CSF+ T cells - Ullrich, Evelyn; Abendroth, Benjamin; Rothamer, Johanna; Huber, Carina; Buettner-Herold, Maike; Kitowski, Vera; Vogler, Tina; Longerich, Thomas; Zundler, Sebastian; Völkl, Simon; Beilhack, Andreas; Rose-John, Stefan; et al. (2018)
EVALuna2:207769

Targeting Inflammatory T Helper Cells via Retinoic Acid-Related Orphan Receptor Gamma t Is Ineffective to Prevent Allo-Response-Driven Colitis - Buchele, Vera; Abendroth, Benjamin; Buettner-Herold, Maike; Vogler, Tina; Rothamer, Johanna; Ghimire, Sakhila; Ullrich, Evelyn; Holler, Ernst; Neurath, Markus; Hildner, Kai (Frontiers in Immunology, 2018)
Intestinal graft-versus-host disease (GvHD) is a life-threatening, inflammatory donor T cell-mediated complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT). In the light of the reported efficacy of interleukin-23 (IL-23)-blockade to mitigate syngeneic intestinal inflammation in inflammatory bowel disease patients, targeting IL-23 and thereby interleukin-17a (IL-17a) producing T helper (Th17) cells as the T cell subset assumed to be mostly regulated by IL-23, has emerged as a putatively general concept to harness immune-mediated mucosal inflammation irrespective of the underlying trigger. However, the role of Th17 cells during allo-response driven colitis remains ambiguous due to a series of studies with inconclusive results. Interestingly, we recently identified granulocyte-macrophage colony-stimulating factor (GM-CSF+) T cells to be promoted by interleukin-7 (IL-7) signaling and controlled by the activating protein-1 transcription factor family member basic leucine zipper transcription factor ATF-like (BATF) as critical mediators of intestinal GvHD in mice. Given the dual role of BATF, the contribution of IL-23-mediated signaling within donor T cells and bona fide Th17 cells remains to be delineated from the regulation of GM-CSF+ T cells in the absence of BATF. Here, we found in a complete MHC class I-mismatched model that genetic inactivation of the IL-23 receptor (IL-23R) or the transcription factor retinoic acid-related orphan receptor gamma t (RORγt) within donor T cells similarly ablated Th17 cell formation in vivo but preserved the T cells' ability to induce intestinal GvHD in a compared to wild-type controls indistinguishable manner. Importantly, RORγt-independent manifestation of intestinal GvHD was completely dependent on BATF-regulated GM-CSF+ T cells as BATF/RORγt double-deficient T cells failed to induce colitis and the antibody-mediated blockage of IL-7/IL-7R interaction and GM-CSF significantly diminished signs of intestinal GvHD elicited by RORγt-deficient donor T cells. Finally, in analogy to our murine studies, colonic RORC expression levels inversely correlated with the presence of GvHD in allo-HSCT patients. Together, this study provides a crucial example of a BATF-dependent, however, IL-23R signaling- and RORγt-, i.e., Th17 fate-independent regulation of a colitogenic T cell population critically impacting the current understanding of intestinal GvHD.
EVALuna2:34273